General health literacy, COVID-19-related health literacy, and protective behaviors: evidence from a population-based study in Japan - Keiko Murakami; Keiko Murakami; Keiko Murakami; Shinichi Kuriyama; Shinichi Kuriyama; Shinichi Kuriyama; Hideki Hashimoto (Frontiers Media S.A., 2023)
IntroductionHealth literacy (HL) can be regarded as a key element of non-pharmaceutical interventions used in emergency responses. The present study aimed to determine the associations of combinations of general HL and COVID-19-related HL with COVID-19 protective behaviors and healthy lifestyle behaviors.MethodsA questionnaire survey was conducted from December 2020 to January 2021 among residents in Japanese metropolitan areas. Valid responses were received from 1,443 residents. The levels of HL were categorized into four groups: low level in both HLs (reference), high level in general HL only, high level in COVID-19-related HL only, and high level in both HLs. The total scores of eight COVID-19 protective behaviors were dichotomized into low and high adherence. Healthy lifestyle behaviors included healthy and balanced diet, adequate sleep, and regular exercise. Poisson regression analyses were conducted to examine the associations between the HL groups and high adherence to COVID-19 protective behaviors.ResultsHigh level in COVID-19-related HL only was associated with high adherence to COVID-19 protective behaviors [prevalence ratio (PR), 1.25; 95% confidence interval (CI), 1.09-1.45], while high level in general HL only was associated with healthy and balanced diet (PR, 1.49; 95% CI, 1.04-2.13), adequate sleep (PR, 1.46; 95% CI, 1.02-2.10), and regular exercise (PR, 2.00; 95% CI, 1.29-3.13). High level in both HLs showed the highest prevalence of high adherence to COVID-19 protective behaviors and healthy lifestyle behaviors.ConclusionThese findings indicate that COVID-19-related HL and general HL can both be considered to enhance protective behaviors.